The Effect of Internal and External Focus of Attention on Acquisition, Retention and Transfer of Dart Throwing in Mentally Retarded Children - Maryam Lotfi; Jalal Dehghanizade; Fateme Sadat Hosseini (رشد و یادگیری حرکتی ورزشی, 2015)
The aim of this study was to investigate the effect of focus of attention on learning dart throwing in mentally retarded children.In this quasi-experimental study, 22 mentally retarded boys (age 10-12 years old) were randomly selected according to IQ (50-70) and were assigned to two homogenous attention (internal, external) groups after the pretest and a training session according to the obtained scores, age and IQ. The subjects practiced in 5 blocks and each block 8 throws. Two-way analysis of variance with repeated measures and ANOVA were used to analyze data. In retention phase, both groups increased accuracy in their throwing (P=0.044). Variability (P=0.044) and throwing accuracy (P=0.047) decreased due to the training. In transfer phase, internal focus group could not transfer skill to new conditions while variable group succeeded to transfer their skill to new conditions. Also, external focus group had lower variability (P=0.049) and higher accuracy (P=0.048) than internal focus group. According to the findings, external focus group was able to retain and transfer skills to new situations which confirmed constrained action hypothesis (Wulf et al., 2001) in mentally retarded individuals.